2018
DOI: 10.1016/j.aquaculture.2018.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Mortality investigation of Mytilus edulis and Mytilus galloprovincialis in France: An experimental survey under laboratory conditions

Abstract: Highlights► M. edulis that survived a mortality outbreak continued to show mortality in the following year, ► Naïve M. edulis adults had significant mortality only when they were in contact with M. edulis that survived a mortality outbreak suggesting a horizontal transmission of a putative causal agent, ► No putative causal agent identified yet, although the bacteria belonging to the Splendidus clade were detected at high prevalence, ► M. edulis spat seems less susceptible than M. edulis adults to mortality, ►… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Results showed that a 'mortality window' opened in all sites during the spring season; similar observations also have been reported recently in France by other researchers (Benabdelmouna et al, 2018;Dégremont et al, 2019). This period corresponded to the spawning season of mussels.…”
Section: Temperature Conditioning and Mortalitysupporting
confidence: 89%
See 2 more Smart Citations
“…Results showed that a 'mortality window' opened in all sites during the spring season; similar observations also have been reported recently in France by other researchers (Benabdelmouna et al, 2018;Dégremont et al, 2019). This period corresponded to the spawning season of mussels.…”
Section: Temperature Conditioning and Mortalitysupporting
confidence: 89%
“…mortalities observed in 2015 in the French Atlantic coast. Furthermore, Benabdelmouna et al (2018) linked the occurrence of a significant percentage of aneuploid hemolymph cells to disseminated neoplasia and concluded that this disease could be viewed as a major cause of morbidity and mortality for French mussels. Elston et al (1988) followed the evolution of this disease over 4 months in M. trossulus; they reported a relatively long dynamic progression of the disease in the early stages (2-3 months) and then a quick evolution when disseminated neoplasia leads to rapid death.…”
Section: Lesions and Alteration: Hemocytic Infiltration Granulocytommentioning
confidence: 99%
See 1 more Smart Citation
“…(Faure et al, 2008). This may suggest that (1) M. galloprovincialis could be less susceptible to the mortality observed on mussel farms than M. edulis, as observed recently under laboratory conditions by Benabdelmouna et al (2018), or (2) the putative causal agents of the mortality are to date only present in these areas and have not spread to other areas yet.…”
Section: Introductionmentioning
confidence: 73%
“…The popularity of mussels owing to their pearling ability and water purification function contributed to a rapid increase in the aquaculture of mussels (Xu, Guo, Xie, & Zhao, 2011). However, with the development of the bivalve culture industry, the frequent occurrence of bivalve disease outbreak has been an important factor that seriously hindered mussel culture (Benabdelmouna et al., 2018; Potasman, Paz, & Odeh, 2002). Bacterial diseases often caused fatal blows at different life stages in mollusks, including bivalves.…”
Section: Introductionmentioning
confidence: 99%